Gene expression of TNF-receptors in peripheral blood mononuclear cells of patients with alcoholic cirrhosis - Hanck, Christoph; Glatzel, Michael; Singer, Manfred V.; Rossol, Siegbert (Journal of hepatology, 2000)
Background/Aims:Elevated concentrations of tumor necrosis factor receptors have been detected in alcoholic cirrhosis, but it remains unknown whether or not peripheral blood mononuclear cells are a source of tumor necrosis factor receptors and reflect the clinical disease activity of patients with advanced alcoholic liver disease. Methods: Twenty-two abstinent patients in different stages of alcohol-induced cirrhosis according to the criteria of the Child-Pugh classification (Child-Pugh stage A: 4, Child-Pugh stage B: 10, Child-Pugh stage C: 8) were compared with four healthy individuals. Semi-quantitative reverse transcriptase-polymerase chain reaction was used for the measurement of the expression of tumor necrosis factor-α, soluble tumor necrosis factor receptors-p55, -p75, interleukin-10 and inducible nitric oxide synthase in unstimulated peripheral blood mononuclear cells. Results: Unstimulated peripheral blood mononuclear cells of patients with alcoholic cirrhosis demonstrate a stage-dependent enhanced RNA expression of tumor necrosis factor-α (healthy controls 0/4, Child-Pugh stage A 2/4, stage B 10/10, stage C 8/8; p<0.01). The mRNA expression of TNF-receptors-p55/-p75 is significantly higher in patients with severe alcoholic cirrhosis (Child-Pugh stage B or C patients) than healthy controls (p<0.05), while peripheral blood mononuclear cells from patients with Child-Pugh stage A show a similiar pattern of gene expression to healthy controls. No significant upregulation of interleukin-10 was found. Inducible nitric oxide synthase was detectable in Child-Pugh stage C (p<0.05). Conclusions: Unstimulated peripheral blood mononuclear cells of patients with severe alcoholic cirrhosis (Child-Pugh stage B and C) demonstrate a systemic leukocyte activation and gene expression of tumor necrosis factor-α and tumor necrosis factor receptors-p55/-p75, which is correlated with the activity of the disease. Our data confirm previous studies that reported a correlation between plasma levels of pro-inflammatory cytokines and the severity of alcoholic cirrhosis. The role of interleukin-10 and inducible nitric oxide synthase in the pathogenesis of alcoholic cirrhosis remains to be fully elucidated.